The Night Gardener : A Novel - Pelecanos, George P. (New York Warner Books, 2006)
When the body of a local teenager turns up in a community garden, veteran homicide detective Gus Ramone teams up with T.C. Cook, a legendary, now retired detective, and Dan "Doc" Holiday, his former partner who left the force under a cloud of suspicion.
Keywords: Teenagers -- Serial murderers -- Serial murderers